2015
DOI: 10.1177/2333794x14567193
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Interrelated Factors in Patients With Congenital Hypothyroidism as Detected by Newborn Screening in Guangxi, China

Abstract: Background. A newborn screening program (NSP) for congenital hypothyroidism (CH) was carried out in Guangxi in order to understand the incidence of CH and the factors interrelated to major types of CH in this region of China. Methods. During 2009 to 2013, data from 930 612 newborns attending NSP in Guangxi were collected. Patients were classified with either permanent CH (PCH) or transient CH (TCH) after 2 years of progressive study. Results. A total of 1210 patients were confirmed with CH with an incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Most of them evaluated the possible risk factors for primary CH. Reported risk factors for transient CH were as follows: iodine deficiency or excess, prematurity, old maternal age, male gender, retinopathy of prematurity, twin pregnancy, maternal autoimmune thyroid disease, intrauterine growth retardation, and cesarean delivery (19,24,26,33,51,56,63). Reported risk factors for permanent CH with dysgenesis of the thyroid gland were as follows: female gender, familial history of CH, birth in geographical areas with a high rate of the disease, old maternal age, ethnicity (Caucasians) but not seasonality (5,15,42,50,56,61).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of them evaluated the possible risk factors for primary CH. Reported risk factors for transient CH were as follows: iodine deficiency or excess, prematurity, old maternal age, male gender, retinopathy of prematurity, twin pregnancy, maternal autoimmune thyroid disease, intrauterine growth retardation, and cesarean delivery (19,24,26,33,51,56,63). Reported risk factors for permanent CH with dysgenesis of the thyroid gland were as follows: female gender, familial history of CH, birth in geographical areas with a high rate of the disease, old maternal age, ethnicity (Caucasians) but not seasonality (5,15,42,50,56,61).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies showed an association between gender and CH. Many reports have indicated that CH is frequently found in girls (12,15,17,6,31,36,44,46,53,56). According to previous studies, the female to male ratio was approximately 1.0 among hereditary cases of CH (31).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The incidence of CH is different among neonates of various countries of the world and ranges from 1:2000 to 1:4000 [2][3][4][5][6], the incidence of CH in different areas of Iran is reported to vary from 1:400 to 1:1000 [7,8].…”
Section: S S E E E E E a A A A A R R R R R C C C C C H P H P H P H P mentioning
confidence: 99%
“…Congenital hypothyroidism (CH) is known as one of the most common preventable causes of mental retardation ( 1 ), and also considered a major preventable and detectable cause of mental retardation with early and simple treatment ( 2 ). CH is caused by dysfunction of the hypothalamus-pituitary- thyroid axis ( 1 ) and lack of thyroid hormones at birth in newborns ( 3 ). Thyroid hormones have an invaluable role in maintaining mental development in children ( 4 ).…”
Section: Introductionmentioning
confidence: 99%